Synthesis and structures of copper(I) complexes with phosphino-functionalized N-heterocyclic carbenes (NHCP) and Bis-N-heterocyclic carbenes (Bis-NHC) - Kühnel, Erik; Rominger, Frank; Oeser, Thomas; Hofmann, Peter (Organometallics, 2012)
New copper(I) complexes bearing N-phosphino- and N-phosphinomethyl-functionalized NHC ligands (NHCP systems) were synthesized and fully characterized. Using halide-containing copper(I) precursors, strikingly different structural motifs were found, dependent on the substitution pattern of the NHCP moiety. An interesting tetranuclear μ4-bridged copper(I) cluster (4b) is formed when CuBr·SMe2 is reacted with the N-phosphino-substituted ligand 1a, whereas the dinuclear complex 4a is formed in an analogous reaction with 1b. Dinuclear metallacycles (2a,b) were isolated and characterized by X-ray diffraction when the halide-free copper(I) precursor [Cu(CH3CN)4]PF6 was reacted with NHCP ligands 1a,b using the N-phosphinomethyl-substituted NHCP ligands 5a,b, as well as employing the bis-NHC ligands BIM and BIM-BMe2 (10a,b), respectively. The observed copper(I)-copper(I) distances are directly correlated with the size of the metallacycle formed. An unexpected strong influence upon the metal-metal separation was found for the charged complexes in 10a,b. Using directly N-tBu-substituted NHCP ligands led to formation of an electronically less favorable trans-C,C coordination at the copper(I) centers (3 and 6a), which inhibited the formation of a dimeric species in the case of 3.
Gesehen am 27.11.2018